The novel kumaraswamy extended garima distribution, statistical properties and its application - Karakas, Ayşe Metin; Karakas, Murat; Doğan, Mine (My University, 2023)
This essay aims to present a novel Kumaraswamy Extended Garima distribution family. We obtain a cumulative distribution function, the failure rate, the risk rate, the inverse risk function, the odd function, the cumulative risk function, the moment r-th, the characteristic function of the moment generating function, the moments, the mean and the variance, Lorenz and Bonferroni curves, order statistics, MLE, mean time between failures (MTBF), Renyi and Tsallis entropies. The MLE technique estimates the parameters of the new Kumaraswamy Extended Garima distribution. The parameters of the MLE technique are derived using a nonlinear system of equations and the Symmetric Information Matrix. Furthermore, the consequences are analogous to others because they are probability distributions. According to the findings, the proposed distribution fits these data sets better than existing probability distributions.
Keywords: Garima distribution; Kumaraswamy distribution; Cumulative distribution function; Characteristic function; Symmetric information matrix.